Evaluating the toxic effects of Ficus infectoria Roxb. and Emblica officinalis Gaertn. leaf extracts on cell division and chromosomal morphology of Cicer arietinum L. - S.S. Khan, A.A. Rather, A. Verma, S. Siddiqui, S. Alamari, M.K. Meghvansi, (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10.5pt; line-height: 110%; font-family: ";Times New Roman";,";serif";; mso-bidi-font-size: 10.0pt; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">In the present study, t<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold; mso-bidi-font-family: 'Times New Roman'; mso-bidi-font-style: italic;">he aqueous extracts of Ficus infectoria and Emblica officinalis leaves were evaluated for their toxic effect on cell division and chromosomal morphology of Cicer arietinum root apical meristem. The extracts were prepared by dissolving 15 gm, 30 gm and 45 gm of dry leaf powder in 1000 ml of double distilled water. The experiment was conducted in sterilized petri dishes. The results revealed that the different concentrations of aqueous extract of F. infectoria and E. officinalis caused cytotoxic and mitodepressive effects on chromosome of Cicer arietinum. The dose–dependent and statistically significant (p<0.05) inhibitation of mitotic index by the extracts were noticed when compared with the control. These results indicate the inhibitory, mitodepressive and turbagenic activities of the aqueous extracts of studied plants on Cicer arietinum.